2020
DOI: 10.1136/archdischild-2020-320107
|View full text |Cite
|
Sign up to set email alerts
|

Solar-powered oxygen, quality improvement and child pneumonia deaths: a large-scale effectiveness study

Abstract: BackgroundPneumonia is the largest cause of child deaths in low-income countries. Lack of availability of oxygen in small rural hospitals results in avoidable deaths and unnecessary and unsafe referrals.MethodWe evaluated a programme for improving reliable oxygen therapy using oxygen concentrators, pulse oximeters and sustainable solar power in 38 remote health facilities in nine provinces in Papua New Guinea. The programme included a quality improvement approach with training, identification of gaps, problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…All studies enrolled children aged <15 years. Six studies included, but not exclusively, patients <2 months old [23][24][25][26][27][28] ; another enrolled only those in this age group. 29 Seven studies included patients aged 2 months to ≤5 years, 23-28 30-32 and only two included children >5 years and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…All studies enrolled children aged <15 years. Six studies included, but not exclusively, patients <2 months old [23][24][25][26][27][28] ; another enrolled only those in this age group. 29 Seven studies included patients aged 2 months to ≤5 years, 23-28 30-32 and only two included children >5 years and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In Papua New Guinea (PNG), Duke et al suggested that the most probable explanation for the observed 35% mortality reduction for children admitted to hospital with pneumonia is “the improved system and better quality of care that accompanies such a system” [ 3 , 6 ]. Following this rationale, subsequent work in Laos and remote clinics in the PNG highlands introduced improved oxygen systems alongside other clinical education and quality improvement activities—not only addressing pneumonia and oxygen therapy, but also many other important aspects of hospital care for children [ 6 , 8 ]. These programs reported substantial mortality benefits for children with pneumonia, and the PNG program also documented substantial benefits for children overall [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this rationale, subsequent work in Laos and remote clinics in the PNG highlands introduced improved oxygen systems alongside other clinical education and quality improvement activities—not only addressing pneumonia and oxygen therapy, but also many other important aspects of hospital care for children [ 6 , 8 ]. These programs reported substantial mortality benefits for children with pneumonia, and the PNG program also documented substantial benefits for children overall [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations